2018
DOI: 10.2172/1504627
|View full text |Cite
|
Sign up to set email alerts
|

Special Analysis: Impact of Updated GSA Flow Model on E-Area Low-Level Waste Facility Groundwater Performance

Abstract: In March 2018, the Savannah River National Laboratory (SRNL) notified Solid Waste Management (SWM) of new information that could potentially impact groundwater (GW) disposal limits and possibly require temporary protective measures (Crowley 2018). GW flow directions in the E-Area Low-Level Waste Facility (LLWF) Slit Trenches (STs), Engineered Trenches (ETs), and the Low Activity Waste Vault (LAWV) have notably changed in the new 2018 General Separations Area (GSA) flow model (Flach 2018a). The 2018 GSA flow mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 6 publications
(17 reference statements)
0
33
0
Order By: Relevance
“…The results of the study showed that simulated and vadose zone plume concentrations are reasonably consistent and that the phased operation of ET 1 and ET 2 is likely to ensure that performance objectives are met. This conclusion was later confirmed by the Special Analysis of the impact of the updated GSA flow model on E-Area groundwater performance (Hamm et al 2018)…”
Section: Engineered Trenchmentioning
confidence: 69%
“…The results of the study showed that simulated and vadose zone plume concentrations are reasonably consistent and that the phased operation of ET 1 and ET 2 is likely to ensure that performance objectives are met. This conclusion was later confirmed by the Special Analysis of the impact of the updated GSA flow model on E-Area groundwater performance (Hamm et al 2018)…”
Section: Engineered Trenchmentioning
confidence: 69%
“…Although CA-related work completed in FY2019 provides indications that the conclusions of the CA are still valid, the 2010 SRS CA should be updated upon revision of the SRS PA(s) to address the number of proposed changes to inventories and sources and model improvements accumulated since the 2010 CA. SRNL-STI-2018-00624, Revision 0 (Hamm et al 2018) CA impact TBD. GW flow directions used in estimating radionuclide transport to surface water (i.e., streams and Savannah River) will need to be updated in the next CA revision.…”
Section: Changes Potentially Affecting the Pa Ca Das Or Rwmbmentioning
confidence: 99%
“…An SA was issued in December 2018 for the E-Area LLWF entitled Impact of Updated GSA Flow Model on E-Area Low-Level Waste Facility Groundwater Performance (Hamm et al 2018). The 2018 GSA flow model had been updated using 20 years of new hydrologic field data and model calibration methods that employed mathematical optimization software.…”
Section: Cumulative Effect Of Changesmentioning
confidence: 99%
“…STI-2018-00624 (Hamm et. al., 2018) The results of this SA provide increased confidence that the planned PA revision will produce acceptable GW limits…”
Section: Srnl-mentioning
confidence: 99%
“…Pending PA annual review affirms that the supporting studies performed in FY2019 do not alter the conclusions of the ELLWF PA (WSRC, 2008) and that there is a reasonable expectation that the ELLWF will meet the performance objectives delineated in DOE Order 435.1. New groundwater flow predictions resulted in the initiation of an SA (Hamm et al, 2018), and measures have been introduced to maintain assurance that performance objectives will continue to be met (see Table 1-1). The number of proposed changes to data, models and operational plans for the ELLWF since the 2008 PA were deemed sufficient to warrant a revision.…”
Section: Completementioning
confidence: 99%